Transient Global Amnesia as an Unusual Presentation of Status Epilepticus: Case Report - Herrera Saldarriaga, Nicolás; Cardozo Ocampo, Alejandro; García Pareja, Manuel A. (Revista del Hospital Italiano de Buenos Aires, 2025)
We present the case of a 71-year-old female patient with symptoms consistent with transient global amnesia secondary to nonconvulsive status epilepticus. She had experienced recurrent episodes over the previous two years. The article describes her clinical progression, relevant considerations for her management, and a brief review of the literature related to transient epileptic amnesia.